Evaluation of IT Resource Management Capability Using COBIT 5 on Subdomain EDM04 and APO07 - Carissa Renatasari; Anita Wulansari; Eristya Maya Safitri (Komunitas Dosen Indonesia, 2025)
The Population and Civil Registration Office of Sidoarjo Regency is a government agency that implements performance-based management, focusing its activities on service excellence and utilizing information technology in its services such as the Population Administration Information System (SIAK) and